Commentary on the third Geneva Convention : treatment of prisoners of war - International Committee of the Red Cross; Dörmann, Knut; Henckaerts, Jean-Marie (Cambridge : Cambridge University Press, 2021)
The application and interpretation of the four Geneva Conventions of 1949 and their two Additional Protocols of 1977 have developed significantly in the seventy years since the International Committee of the Red Cross (ICRC) first published its Commentaries on these important humanitarian treaties. To promote a better understanding of, and respect for, this body of law, the ICRC commissioned a comprehensive update of its original Commentaries, of which this is the third volume. The Third Convention, relative to the treatment of prisoners of war and their protections, takes into account developments in the law and practice in the past seven decades to provide up-to-date interpretations of the Convention. The new Commentary has been reviewed by humanitarian law practitioners and academics from around the world. This new Commentary will be an essential tool for anyone involved with international humanitarian law.
Title from publisher's bibliographic system (viewed on 23 Aug 2021).
Keywords: Convention Relative to the Treatment of Prisoners of War -- (1949 August 12); Prisoners of war -- Legal status, laws, etc; War (International law)